TRANSLATION OF OIL AND GAS - RELATED ENGLISH PHRASES - Badalova Luiza Kholmamatovna (Bright Mind Publishing, 2025)
The challenges of translating oil and gas-related terminologies into English are taken into account. Technical texts' genre and style attract attention. The primary challenges associated with translating this vocabulary are examined. According to the authors' research, translating texts about oil and gas calls for particular specialized instruction and thorough familiarity with both the target and target languages.
Keywords: Translation, terminology, challenges, translation strategies, optimal development, oil and gas sector, oil field development, drilling a field.